A Quick Diagnosis Tool to Predict Dense Media Cyclone Performance & Root Cause Identification for Troubleshooting on Real Time Basis - Bhargav Dhavala; Sristy Raj; Suman Krishna Sit; Adity Ganguly; D. P. Chakraborty; Ashok Kumar (International Mineral Processing Congress, 2018)
"Tatasteel’s West Bokaro washery#3 is designed to deslime raw coal at 0.5mm; the oversize (+0.5mm) is beneficiated in dense media cyclones (DMC) while the undersize (-0.5mm) is beneficiated in froth flotation (FF) cells. Nearly, 80% of the raw coal feed reports to the DMC circuit consisting of four parallel streams. Presently, the performance of DMCs at washery#3 is interpreted by: (a) comparing the actual plant yield w.r.t the lab predicted yield and (b) misplacement of clean coal to middllings.However, the comparison between actual & lab predicted yield is fallacious given the fact that the lab predicts yield of the borehole sample while the feed received at the plant has different characteristics altogether due to the dilution during mining. To mitigate the said limitations, a quick diagnosis tool using the past data has been developed that will give a prediction of performance of different coal seams in the DMCs, inputs being feed ash to DMCs and stream wise feed specific gravity (coal & magnetite combined).The tool also will help in identifying the root cause on real time basis thereby helping the operator to take necessary corrective actions. The operator can intimate the mining personnel in cases of shale reporting to the feed as a result of dilution during mining. In events of higher standard deviations between the parallel streams w.r.t feed specific gravity, the operator can adjust the parameters accordingly to minimize the yield loss. INTRODUCTION West Bokaro came into existence in 1948, as an independent coal company, managed by M/S Anderson Wright. Tata Steel acquired the Company in 1956 to meet its requirement of metallurgical grade coal for Iron making. Subsequently, in 1976, it was made a division of Tata Steel. In 1974, when coal mines were nationalized, West Bokaro was exempted as it produced coal only for captive consumption of the Steel Works. The first washery of India was set up in West Bokaro. The business objective of the West Bokaro division is to produce clean coal at optimum cost for captive use in the steel plant of Tata Steel at Jamshedpur. The strategy is to reduce ash with minimum loss of yield so that quality of coal improves and yet the cost is beneficial vis-a vis imported coal. The primary product is the metallurgical grade coal for coke ovens, which converts coal into coke for use in the Blast Furnaces."